Nicht organische Sehstörungen - Steffen, Heimo (Augenheilkunde up2date, 2018)
Nicht organische Sehstörungen sind in der augenärztlichen Praxis eine häufige Herausforderung. Im Kindesalter ist die häufigste Störung eine beidseits unklare Visusreduktion, im Erwachsenenalter eher eine einseitige Sehstörung. Dieser Beitrag soll den Augenarzt für Patienten mit nicht organischer Sehstörung sensibilisieren und einen Überblick über diagnostische Strategien bei Patienten mit dieser vermuteten Diagnose geben.Non-organic visual loss is a frequent challenge in ophthalmic practice. In children most patients are prepubertal females. The most frequent manifestation in this age-group is a bilateral unexplained decrease of visual acuity. In adulthood patients often indicate a degree of visual loss after an accident or a disease – that could not be explained by the eye condition alone. Non-organic visual loss may be frustrating for both, patients and physicians. The aim of the present article is to sensitize ophthalmologists to this condition and to provide a diagnostic frame and strategy how to manage patients with such a diagnosis.
Keywords: unklare Visusreduktion; funktionelle Sehstörung; Diagnostik